Bio‐based Mg(OH)2@M‐Phyt: improving the flame‐retardant and mechanical properties of flexible poly(vinyl chloride). Issue 10 (24th July 2019) - Meng, Weihua; Wu, Weihong; Zhang, Weiwei; Cheng, Luyao; Han, Xiangzhuo; Xu, Jianzhong; Qu, Hongqiang
Abstract: Two novelty bio‐based multifunctional metallic phytate coated (M‐Phyt, M ≡ Cu, Zn) Mg(OH)2 (MH@M‐Phyt) were designed and incorporated into flexible poly(vinyl chloride) (PVC). MH@M‐Phyt was incorporated into PVC materials in a powder form. The morphology of the interface between MH and M‐Phyt and their binding states were characterized by TEM and X‐ray photoelectron spectroscopy (XPS), respectively. The TEM images of MH@M‐Phyt indicated that M‐Phyt was successfully coated on the MH surface. Additionally, from the XPS spectra M‐Phyt and MH were connected by Mg–O–P bonds. The flame retardancy and mechanical properties of the PVC composites were investigated through the limiting oxygen index, cone calorimetry and mechanical tests. The char residues were analyzed by SEM. The results revealed that the MH@M‐Phyt powder functioned well in PVC, with a flame retardancy, smoke density, tensile strength and elongation at break better than those of PVC/MH. With 10 phr loading, the peak heat release rate of PVC/MH@Zn‐Phyt and PVC/MH@Cu‐Phyt decreased by 33.5% and 24.6%, respectively, benefitting from the formation of firmer and denser char layers on the char residues. © 2019 Society of Chemical Industry Abstract : Novel halogen‐free bio‐based materials Mg(OH)2 @M‐Phyt were fabricated and were incorporated into flexible poly(vinyl chloride) (PVC). The flame retardancy and smoke suppression of the composites were improved dramatically.